Sudden Cardiac Death in Three Generations of the Same Family: A case report - Khan, MM Zahurul Alam; Chowdhury, Abdul Wadud; Khan, Tunaggina Afrin; Amin, Md Gaffar; Alam, Md Nur; Sabah, Khandaker Md Nurus; Saleh, Mohammed Abaye Deen (Cardiovascular Journal, 2015)
Every one of us has heard about tragic and sudden death of a healthy young person and which is often stated as inexplicable. The current case report focuses on a 20 year old young man with hypertrophic cardiomyopathy facing premature death with history of similar sudden premature death of his grandmother, father and brother. Hypertrophic cardiomyopathy is the commonest cause of sudden cardiac death in young adults and is also an important substrate for heart failure disability at any age. Cardiovasc. j. 2015; 8(1): 73-77